Dynamic of end-tidal carbon dioxide pressure during cardiopulmonary exercise testing before and after heart transplantation - I. Yu. Loginova; O. V. Kamenskaya; A. M. Chernyavskiy; D. V. Doronin; S. A. Alsov; V. N. Lomivorotov (Вестник трансплантологии и искусственных органов)
Aim: to assess the dynamic and prognostic significance of the end-tidal carbon dioxide pressure (PetCO2) during cardiopulmonary exercise testing in recipients before and after heart transplantation (HT).Materials and methods. The study included 55 patients with severe chronic heart failure (CHF) from the HT waiting list. All patients underwent cardiopulmonary exercise testing before and in the long-term follow-up after TS, including determination of PetCO2 at rest and during exercise.Results. Physical capacity, the efficiency of pulmonary ventilation and gas exchange in the long-term after the HT significantly improved compared with the preoperative data. Peak oxygen consumption before and after HT was 10.8 (9.4-11.7) ml/min/kg and 18.9 (18.2-21.0) ml/in/kg (p = 0.020), respectively, the value of the VE/VCO2 slope decreased from 38 (34-45) to 32 (30-36), p = 0.017. PetCO2 at rest before the HT was below the norm, amounted to 30 (28-32) mm Hg, increased to the anaerobic threshold by an average of 3.6 (0.2-5.2)%. After the HT, the level of PetCO2 at rest did not change significantly, but the increase during exercise was 7.6 (3.2-9.4)% (p = 0.001). It was shown that a low baseline PetCO2 value and the absence of its increase during cardiopulmonary exercise test significantly increase the risk of adverse outcome in patients with severe CHF before and after HT (OR 0.62 (0.35-0.87), p = 0.035 and, 16 (0.10-0.24), p = 0.002, respectively).Conclusion. Heart transplantation in patients with severe CHF leads to a significant improvement in the efficiency of pulmonary ventilation and gas exchange in the long-term follow-up. Estimation of the PetCO2 level at rest and during exercise is a promising predictor of adverse outcomes risk stratification in patients with severe CHF before and after HT.